2019
DOI: 10.4103/ija.ija_42_19
|View full text |Cite
|
Sign up to set email alerts
|

Chronic pain following thoracotomy for lung surgeries: It's risk factors, prevalence, and impact on quality of life - A retrospective study

Abstract: Background and Aims: Chronic post thoracotomy pain (CPTP) is a nagging complication and can affect quality of life (QOL). Studies conducted across globe have found a wide variability in the risk factors predisposing to chronic pain following thoracotomy. As no study on CPTP is available from India, we aim to detect the prevalence of CPTP, assess the predisposing factors implicated in its causation and study the impact of CPTP on QOL. Methods: After obtaining clearance f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
21
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(22 citation statements)
references
References 34 publications
1
21
0
Order By: Relevance
“…Bayman and Brennan [ 5 ] reported that more than half of patients suffered CPTP; thus, it seriously influenced community health. Previous studies [ 6 10 ] have found that CPTP was influenced by age, sex, diabetes, properties of tumor, type of surgery, duration of chest tube drainage, and so on; nevertheless, these influencing factors relatively lack repeatability of studies. Although CPTP is one of the great burdens in community health, the mechanism of CPTP is still unknown; hence, the tracing of the predictors or risk factors of CPTP is particularly important for prevention and prediction.…”
Section: Introductionmentioning
confidence: 99%
“…Bayman and Brennan [ 5 ] reported that more than half of patients suffered CPTP; thus, it seriously influenced community health. Previous studies [ 6 10 ] have found that CPTP was influenced by age, sex, diabetes, properties of tumor, type of surgery, duration of chest tube drainage, and so on; nevertheless, these influencing factors relatively lack repeatability of studies. Although CPTP is one of the great burdens in community health, the mechanism of CPTP is still unknown; hence, the tracing of the predictors or risk factors of CPTP is particularly important for prevention and prediction.…”
Section: Introductionmentioning
confidence: 99%
“…to be less painful compared with a regular thoracotomy because it is less invasive, however, incidence and severity of CPSP have been reported to be similar. 8 CPSP after thoracic surgery has been associated with a lower overall quality of life, [9][10][11][12][13] and chronic pain is associated with an increased utilisation of healthcare, increased absenteeism and decreased work-related effectiveness. [14][15][16] The direct health-related costs of chronic pain have been reported to be US$11 846 annually, 17 and the indirect work-related costs have been reported to be US$29 617 annually.…”
Section: Open Accessmentioning
confidence: 99%
“…Systematic reviews, meta-analysis and randomised controlled trials occupy the highest position in evidence-based medicine, but in spite of this academic awareness, authors are nowadays resorting to quick research recipes like retrospective studies and online surveys. [ 3 ] The small number of meta-analyses[ 4 5 6 ] and large number of surveys[ 7 8 9 10 11 ] and retrospective studies[ 12 13 14 15 16 17 18 19 20 21 22 23 24 25 26 ] published in the IJA in the last few years are an evidence to this. The commonly known inverse ratio of quantity to quality has also been equally observed at IJA with this enhanced submission process.…”
mentioning
confidence: 99%